IMPLEMENTASI METODE SWOT PADA ANALISIS JARINGAN AREA LOKAL SEKOLAH - Andy Dharmalau; Harun Ar-Rasyid; Muhammad Affan Iskandarsyah (Institut Teknologi dan Bisnis Swadharma, 2022)
The Computer networks as a medium of data communication are currently increasing along with the development of the business world, trade, and education. SMK Bina Karya is an educational institution in the field of business and management where information technology is needed so that learning activities and administrative services run effectivel and effisien. For that we need a computer network. This network device allows the connection of information users remotely. To create a network, it is necessary to understand the concept of computer network topology that will be applied, because the type of topology that will be applied affects the speed of data communication. Local Area Network (LAN) is used as a transmission medium to conduct data transactions between computers and share printers so that it can make work easier. After setting the IP address, training IT Staff in the internal school and tidying up the cable layout, data transmission can run smoothly